Impact of Parent's Divorce on Children's Education for Disability Kids - Gangsar Ali Daroni; Abdul Salim; Sunardi Sunardi (The Center for Disability Studies and Services Brawijaya University, 2018)
Children with special needs are children who have abnormalities in him, thus causing the individual has a need to be tailored to their specific characteristics. Abnormalities of children with special needs, impact on the immediate environment of children, namely family. Many cases of divorce in parents who have children with special needs. The cause may be possible because of negative parents' perceptions of children, low acceptance and resilience in parents with special needs children. Divorced parents have a negative impact on the education of children with special needs, because they lose the ability to fully play a parent in fulfilling the rights of the child. One solution in dealing with divorce that occurs in parents who have children with special needs is to use family counseling and divorce therapy. Handling is expected to minimize the negative impact of divorce parents of children with special needs and prevent the occurrence of divorce cases in other families who have children with special needs.